Dimensions of Adolescent Civic Reasoning: An Examination of Individual Differences. Issue 3 (May 2020) - Alvis, Lauren M.; Metzger, Aaron
The current study examined sociodemographic characteristics and political discussion as correlates of adolescents' qualitative understanding of three civic behaviors. Participants were 743 adolescents ( M age = 15.87, range = 13-20; 55.6% female; 89.9% White) from a midsized city and a small rural town in an Appalachian state. Open-ended responses to three civic behavior scenarios, asking participants why should people protest, vote, and volunteer were content coded (28 codes total). Anecdotal statements are provided to illustrate the variety of themes that emerged among adolescents' written responses. Adolescents applied domain-specific reasons (moral, conventional, and personal) for specific types of civic behavior. Structural justifications were provided for all three civic behaviors, suggesting that many adolescents reason about the broader, structural impact of civic behaviors. In probit regression models, coding categories were differentially associated with adolescent demographic characteristics and political discussion. Findings offer insight into youth's divergent understanding of different forms of civic responsibility and shed light on individual differences in youth's developing civic beliefs.